Penggunaan Ester Asam Fumarat Oral Dalam Pengobatan Kasus Dermatologi - Elina Rahma; Dwi Indria Anggraini (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Introduction: Oral fumaric esters acid (FAE) are interesting compounds in the field of dermatology. FAE works on skin cells and cytokine tissue. So far only a mixture of dimethylfumarate (DMF) and monoethylfumarate (MEF) has been approved for oral treatment of moderate to severe plaque psoriasis. Objective: To determine the use of oral fumaric acid esters (FAE) in the treatment of dermatology Method: The article was prepared using the literature review method, involving 34 literature sourced from books and journals. Results: DMF appears to be a major active component. It is important to emphasize the difference between fumaric acid and fumaric acid esters. Fumaric acid formulations are available as health supplements and are often marketed as natural alternative medicines for treating psoriasis. However, it is poorly absorbed by the intestine and excreted through urine without having any therapeutic effect. Discussion: Although the mode of action of FAE and its mechanism of action in psoriasis therapy is still unclear, the evidence shows that it has nothing to do with the Krebs cycle and the main active compound DMF. There is evidence that FAE is not only effective and safe in psoriasis but also non-granulomatous infectious diseases like annulare granulomas, necrobiosis lipoidica, and sarcoidosis. In vitro and animal studies show some activity in malignant melanoma as well. Conclusion: Oral fumaric acid (FAE) esters are widely used in some dermatology cases. Keywords: Dermatology, fumaric acid, psoriasis, sarcoidosis